PERUBAHAN TUTUPAN LAHAN HUTAN LINDUNG GUNUNG GUNTUR TAHUN 2014 SAMPAI DENGAN TAHUN 2017 - Prasetyo Widodo; Abdul Japar Sidik (Wanamukti: Jurnal Penelitian Kehutanan, 2018)
High pressure by community activities on the existence of forests, especially protected forests that affect the quality of the environment that can cause a disaster, such as the occurrence of flash floods that occurred in 2016 in Garut regency, cannot be separated from damage to the upstream cover of cimanuk-citanduy. This prompted investigators to analyze the three year change of land protection prevailing in Mt. Guntur RPH Simpang BKPH Bayongbong. The objective of research is to calculate how large changes land cover area in Mt. Guntur Protected Area (MGPA), RPH Simpang BKPH Bayongbong KPH Garut in three years. The data collected on July to August 2017 by geographic information system (GIS) and satellite image. The results of land cover interpretation by landsat 8 OLI image 2014 and 2017 describe the condition of land use and land cover change in MGPA. Land cover of MGPA dominated by shrub (B) is 287.58 Ha (57.52%) at 2014 and 202.89 Ha (40.58%) at 2017, so deforestation as three years is 31.24 Ha or 32.13%. The results of ground check there is a land use change to open land and farming dryland. According to data of image interpretation at 2017, the open land is 20.03 Ha but after ground checking is 20.51 Ha. The reduction of it based on data of image interpretation at 2017 is 200.33 Ha to 201.85 Ha after ground checking.